Positive Association Between Location of Melanoma, Ultraviolet Signature, Tumor Mutational Burden, and Response to Anti–PD-1 Therapy. (16th December 2021) - Dousset, Léa; Poizeau, Florence; Robert, Caroline; Mansard, Sandrine; Mortier, Laurent; Caumont, Charline; Routier, Émilie; Dupuy, Alain; Rouanet, Jacques; Battistella, Maxime; Greliak, Anna; Cappellen, David; et al.
Abstract : PURPOSE: Emerging evidence suggests a correlation between the tumor mutational burden (TMB) and the response to programmed cell death-1 protein (PD-1) monotherapy across multiple cancer types. In skin cancers, as high TMB is mostly because of ultraviolet (UV) exposure, we hypothesized a correlation between the primary melanoma cutaneous location according to sun exposure and response to anti–PD-1 monotherapy. METHODS: The aim of this study was to analyze, in advanced melanoma, the relationship between TMB, locations according to sun exposure, and response to PD-1 inhibitors. We conducted a prospective multicentric analysis, by sequencing the most recent metastatic sample before PD-1 inhibitors using FoundationOne assay. RESULTS: One hundred two patients were included, with TMB available for 94 cases. In univariate and multivariate linear regression, TMB was significantly associated with sun-exposed areas of the primary melanoma location and with age (coefficients of the association with log-TMB: non-UV location, –1.05; chronic sun-exposed area, 1.12; P value for the location, < 10 –5 ; age, 0.021 per year, P value for age, .002). Molecular UV signature present on the metastatic site was associated with higher TMB ( P = .003). Melanomas bearing a high TMB had a higher probability of response to PD-1 inhibitors compared with melanomas with a low TMB, with a dose-dependent effect following an exponential curve and a negative odds ratio of 0.40 (95% CI, 0.20 to 0.72, P = .004) between log-TMB and 6-month progression. CONCLUSION: Cumulative sun exposure related to skin location and molecular UV signature present on the metastatic site appear to be relevant biomarkers directly linked to TMB. Because TMB is not yet available to all for routine clinical use, the location of the primary melanoma in a sun-exposed area may play an important role in clinical decisions regarding therapeutic choice. Abstract :